Sustainability for the festival policy: Focused on community and visitors - Shinyoung Kang; Kyoung-Bae Kim (Global Business & Finance Review (GBFR), 2023)
Purpose: To explore the evaluation between tourists' and residents' satisfaction with the tool of Importance-Satisfaction Analysis originally introduced by Importance-Performance Analysis. Design/methodology/approach: A survey was conducted at Anseong Matchum Land, the venue of the festival, and respondents were selected by the convenience sampling method. Also, rest areas at the festival site were used for data collection and 309 out of 400 were judged to be valid. Included in the questionnaires was a series of Likert-type questions about the respondent's satisfaction with 18 attributes of the festival and the importance of these attributes to overall satisfaction with the festival. Findings: The results of this research show that the average degree of importance for the 18 attributes is 3.89, and the degree of satisfaction is 3.02. The result identified that parking lot, rest area, and washroom were found included in "Concentrate Here" quadrant of the ISA matrix as needed to prior management in this festival. Research limitations/implications: This study tried to look into local heritage festival regarding comparative perception between festival goers and local residents with ISA to provide that actual problems and potential solutions to the decision-makers of the city to make a sustainable festival. However, it is difficult to extend the results of this festival to other festivals and further research is needed in the future. Originality/value: This research tried to find out the gap between perceived Importance and Satisfaction and to identify actual management problems regarding facilities and services of the festival by ISA analysis originally introduced by Importance-Performance Analysis. This study suggested what festival organizers should prepare for the festival that will be activated after the Covid 19 pandemic.
Keywords: 650; Festival policy; tourist's satisfaction; Importance-Performance Analysis (IPA); Importance-Satisfaction Analysis (ISA)